Randomised clinical study: comparison of acceptability, patient tolerance, cardiac stress and endoscopic views in transnasal and transoral endoscopy under local anaesthetic. Issue 5 (9th July 2014) - Alexandridis, E.; Inglis, S.; McAvoy, N. C.; Falconer, E.; Graham, C.; Hayes, P. C.; Plevris, J. N.
Summary Background Transnasal endoscopy (TNE) with ultrathin endoscopes has been advocated as an attractive alternative, for diagnostic upper endoscopy. Aim To assess tolerability, acceptability and quality of TNE, in comparison with standard upper endoscopy (SOGD, standard oesophago‐gastro‐duodenoscopy) under local anaesthetic. Methods We prospectively recruited 157 patients (83 females/74 males) mean age 57 years. The Fujinon EG530N (5.9 mm) and EG530WR (9.4 mm) endoscopes were used. The endoscopist and all patients completed detailed questionnaires regarding tolerability, acceptance and quality of endoscopy using standard visual analogue scales (VAS). Oxygen saturation (SaO2), heart rate (HR) and systolic blood pressure (SBP) were recorded. Quality of biopsies was evaluated. Results Analysis included 161 procedures (TNE:79, SOGD:82) with duodenal intubation achieved in all patients. VAS scores for patient comfort were significantly better in the TNE group (7.3 vs. 5.3 respectively, P < 0.001). Twenty patients with previous experience of standard endoscopy were randomised to TNE and 19 of them (95.5%) preferred the TNE. Gagging was significantly less in the TNE group (0.12 vs. 3.41 respectively, P < 0.001). Cardiovascular stress was significantly less in the TNE group irrespective of the degree of gagging or comfort. TNE biopsies were smaller, but adequate for definitive diagnosis, similarly to standard endoscopy. Conclusions Transnasal endoscopy is superior to SOGD in terms of comfort and patient acceptance with significantly less cardiovascular stress. TNE can routinely be used as alternative to SOGD under local anaesthetic, for diagnosis and should be preferentially offered in cardiorespiratory compromised patients.